Evaluating Corrosion and Scaling Potential of Drinking Water Supplies in Juybar, North of Iran - Abdoliman Amouei; Hosseinali Asgharnia; Hourieh Fallah; Somayyeh Miri; Habibe Momeni (علوم بهداشتی ایران, 2017)
Background & purpose: One of the major factors in the quality of drinking water is corrosion and scaling. The aim of the present study was to evaluate corrosion and scaling potential of drinking water supply network in Juybar (A city in Iran).